2006
DOI: 10.1111/j.1745-3933.2006.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

A stability study of Pluto's moon system

Abstract: The dynamical structure of the orbital element space of the Pluto–Charon system is studied in the model of the spatial circular restricted three‐body problem by using numerical methods. With the two newly discovered small satellites S/2005 P1 and S/2005 P2, the Pluto–Charon system can be considered as the first known binary system in which celestial bodies move in P‐type orbits. It is shown that the two satellites are in the stable region of the orbital element space and their origin by capture is unlikely. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 17 publications
4
34
0
3
Order By: Relevance
“…Moreover, most of the regions that we probed are dynamically unstable, due to the gravitational effects of the satellites, see Fig. 3 and Nagy et al (2006);Pires Dos Santos et al (2011). Thus, our lack of detection of sub-km moonlets is most probably the consequence of the larger satellites perturbations that ejected the smaller bodies, rather than the effect of a peculiar shallow cumulative size distribution with index q = 2.1.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Moreover, most of the regions that we probed are dynamically unstable, due to the gravitational effects of the satellites, see Fig. 3 and Nagy et al (2006);Pires Dos Santos et al (2011). Thus, our lack of detection of sub-km moonlets is most probably the consequence of the larger satellites perturbations that ejected the smaller bodies, rather than the effect of a peculiar shallow cumulative size distribution with index q = 2.1.…”
Section: Resultsmentioning
confidence: 81%
“…Our results are Tholen et al (2008) for Charon, Nix and Hydra, and from Showalter et al (2011Showalter et al ( , 2012 for P4 and P5, and are indicated by the vertical dotted lines. The radii R unst,S (in Plutocentric distance, dashed line) is the boundary inside which stable S-orbits can exist around Pluto (Nagy et al 2006). Grey zones are regions of stability allowed by Nix and Hydra (Pires Dos Santos et al 2011). summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations